Perancangan Aplikasi Chatbot Menggunakan Wit.Ai pada Sistem SPP-IRT Berbasis Web - Alfiat, Bagus Fatwan; Eosina, Puspa; Al Ikhsan, Safaruddin Hidayat (Jurnal Informatika Universitas Pamulang, 2021)
SPP-IRT is a system of BPOM agencies that implements consulting services for users who are applied using live chat.Â  Judging from the SPP-IRT live chat administrator, there were 254 unserved messages out of 665 messages, and included out-of-hours incoming messages. Judging from the data, SPP-IRT live chat has quite dense traffic. Therefore, it is necessary to create a chatbot that is able to answer questions automatically. Chatbots are designed to be able to communicate with humans using Natural Language Processing (NLP). This chatbot is built with Node.Js and leverages Wi.ai for a knowledge base. Wit.ai is a machine built with NLP. The steps taken in this research start from data collection, analysis, knowledge base design, system design, program creation, testing andÂ  system application. This research data was obtained from SPP-IRT related FAQs. The results obtained that chatbots are able to provide diverse responses in accordance with data that has been trained and validated through Wit.ai.